Influence of Must Supplementation on Growth of Pediococcus spp. after Alcoholic Fermentation - Wade, M.E.; Osborne, J.P.; Edwards, C.G. (South African Journal of Enology and Viticulture, 2018)
One factor potentially affecting growth of wine spoilage microbes (e.g., Pediococcus spp.) is the presence of nutrients not consumed during alcoholic fermentation by Saccharomyces cerevisiae. To assess the impact of must nutrient supplementation on Pediococcus spp., synthetic grape musts containing low (55.2 mg N/L), medium (250 mg N/L), or high (530 mg N/L) concentrations of yeast assimilable nitrogen (YAN) were fermented by S. cerevisiae. Upon cessation of fermentative activity P. damnosus OW-2, P. inopinatus OW-8, P. parvulus WS-7C, WS-29A, OW-1, or P. pentosaceus ATCC 33316 were inoculated at 104 to 105 cfu/mL. With the exceptions of OW-1 and OW-2, none of the other species or strains grew in the synthetic wines unless yeast extract or peptone was added, suggesting the absence of an essential nutrient. Experiments were replicated using Cabernet Sauvignon musts containing low (66.9 mg N/L), medium (219 mg N/L), and high (438 mg N/L) YAN. In general, wines containing the greatest residual amino acid concentrations (high YAN) supported better growth of the aforementioned Pediococcus spp. However, low YAN wines containing negligible residual nitrogen achieved similar populations after a short period of initial inhibition, suggesting that ‘excessive’ nitrogen supplementation to musts does not have a large impact on growth of pediococci post alcoholic fermentation.